Tactics and resistances in digital communication: a rereading of Michel de Certeau - Karam, Tanius (2025)
This article reexamines the thought of Michel de Certeau from a communication studies perspective. One of its main objectives is to analyze his contribution to the study of resistance as symbolic and practical reappropriation in everyday life; likewise, it establishes a dialogue with other critical traditions—Gramsci, Foucault, Scott, Abu-Lughod, and Bonfil Batalla—in order to reconstruct the notion of tactics within the Latin American field of communication and to highlight its impact on the shift from transmission-centered models toward approaches focused on mediations, social uses, and the active production of meaning by subjects.Based on this theoretical framework, the article proposes a rereading of resistance applied to digital environments through the analysis of practices such as memes, lurking, algorithmic disobediences, and the communal reappropriation of technologies. It is argued that everyday tactics make it possible to understand forms of creativity, negotiation, and micro-resistance in contexts of algorithmic surveillance, without necessarily idealizing their emancipatory potential. Finally, lines of research are proposed for the study of digital tactics using methodologies specific to communication studies.